Evaluasi dan pengembangan asas-asas kurikulum pendidikan Islam: Asas filosofis dan asas sosiologis di SD Negeri 10 Sabang, Aceh - Sidiq, Heri Purwanto (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2023)
Curriculum evaluation and development is very important in education. This needs to be done to improve the quality of the curriculum and the output of learners in accordance with instructional objectives. This research uses descriptive qualitative methods to look at the evaluation process and the development of curriculum principles at SD Negeri 10 Sabang, Aceh. The results of the analysis show that the evaluation process has been running well, the aspects of the curriculum that are evaluated include curriculum content, teaching strategies, teaching media, and the results achieved. In addition, this study also identified the philosophical principles applied in the curriculum of SD Negeri 10 Sabang, namely the progressivism school of philosophy. The curriculum development of SD Negeri 10 Sabang has paid attention to philosophical principles and sociological principles in its preparation. Evaluation and development of the curriculum needs to be carried out continuously so that the curriculum can be improved from year to year. Abstrak Evaluasi dan pengembangan kurikulum merupakan hal yang sangat penting dalam dunia pendidikan. Hal ini perlu dilakukan untuk memperbaiki kualitas kurikulum dan output peserta didik sesuai dengan tujuan instruksional. Penelitian ini menggunakan metode kualitatif deskriptif untuk melihat proses evaluasi dan pengembangan asas-asas kurikulum di SD Negeri 10 Sabang, Aceh. Hasil analisis menunjukkan bahwa proses evaluasi telah berjalan dengan baik, aspek kurikulum yang dievaluasi mencakup isi kurikulum, strategi pengajaran, media pengajaran, dan hasil yang dicapai. Selain itu, penelitian ini juga mengidentifikasi asas filosofis yang diterapkan dalam kurikulum SD Negeri 10 Sabang, yaitu aliran filsafat progressivisme. Pengembangan kurikulum SD Negeri 10 Sabang sudah memperhatikan asas filosofis dan asas sosiologis dalam penyusunannya. Evaluasi dan pengembangan kurikulum tersebut perlu terus dilakukan agar kurikulum tersebut dapat ditingkatkan dari tahun ke tahun.